CLB add-on treatment in patients with epileptic encephalopathy: a single center experience with long-term follow-up - TÜRKDOĞAN, DİLŞAD (SPRINGER HEIDELBERG, 2022)
Clobazam (CLB) is an effective anticonvulsant used as an adjunctive treatment for several seizures and epilepsy syndromes. Data are limited on efficacy and safety of CLB as add-on therapy for epileptic encephalopaties (EEs) other than Lennox-Gastaut syndrome (LGS). This retrospective study aimed to assess efficacy and safety of long-term CLB add-on therapy for various EE syndromes. Data on CLB add-on therapy were assessed in 74 children (60.8% male) after 3 months (early) and 12 months (late) follow-up as well as in 57 (77%) patients who had been on CLB therapy longer than 12 months (mean:39.11 +/- 30.29; range:12-129 months) (very late) were reported. Data on CLB add-on therapy were assessed in 74 children (60.8% male) after 3 months (early) and 12 months (late) follow-up as well as in 57 (77%) patients who had been on CLB therapy longer than 12 months (mean:39.11 +/- 30.29; range:12-129 months) (very late) were reported. Good response rate (> 50%) for seizures was achieved in 24% at early follow-up, 30% at late follow-up, and 35% during very late follow-up. Complete seizure remission was achieved for 15% seizures; 72.7% occurred at very late follow-up. Myoclonic seizures were the most responsive (35%); this response increased during late follow-up (46%), whereas 27.3% of myoclonic-atonic/atonic seizures had good response at early and very late follow-up. At late follow-up, comparison of mean effective doses of CLB did not show significant difference among types of seizures with good response. Adverse effects reported in 15% of patients did not require stopping CLB therapy. Generalized epileptogenic potentials significantly decreased while focal epileptogenic potentials significantly increased at first year of treatment in comparison to basal EEG findings (p < 0.001). CLB should be considered as an optional antiepileptic that is well tolerated, particularly in EEs with myoclonic and myoclonic-atonic/atonic seizures.
Keywords: Clobazam; Efficacy; Epileptic encephalopathies; Tolerance; Myoclonic-atonic; atonic seizures; safety